Balancing Strength and Flexibility: How the Synthesis, Organization, and Modification of Guard Cell Walls Govern Stomatal Development and Dynamics - Rui, Yue; Chen, Yintong; Kandemir, Baris; Yi, Hojae; Wang, James Z.; Puri, Virendra M.; Anderson, Charles T. (Frontiers in Plant Science, 2018)
Guard cells are pairs of epidermal cells that control gas diffusion by regulating the opening and closure of stomatal pores. Guard cells, like other types of plant cells, are surrounded by a three-dimensional, extracellular network of polysaccharide-based wall polymers. In contrast to the walls of diffusely growing cells, guard cell walls have been hypothesized to be uniquely strong and elastic to meet the functional requirements of withstanding high turgor and allowing for reversible stomatal movements. Although the walls of guard cells were long underexplored as compared to extensive studies of stomatal development and guard cell signaling, recent research has provided new genetic, cytological, and physiological data demonstrating that guard cell walls function centrally in stomatal development and dynamics. In this review, we highlight and discuss the latest evidence for how wall polysaccharides are synthesized, deposited, reorganized, modified, and degraded in guard cells, and how these processes influence stomatal form and function. We also raise open questions and provide a perspective on experimental approaches that could be used in the future to shine light on the composition and architecture of guard cell walls.